Innovation, industrial dynamics and economic growth - Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2015)
We present a class of dynamic general-equilibrium models of education, innovation and technology transfer to explain the evolution of industries and aggregate growth in closed and open economies. Firms employ educated workers in order to develop higher-quality products. The realization of quality innovations becomes more difficult as the quality level increases but this deterioration of technological opportunities is compensated by an improvement of the researchers' capabilities. Innovation and human-capital accumulation appear as in-line engines of scale-invariant endogenous growth. Industries evolve according to stochastic processes of innovation, imitation and technology adaption in the global economy.
urn:nbn:de:bsz:21-dspace-642199
Keywords: F43; O31; O33; O34; 330; education; innovation; industrial dynamics; technology transfer; international trade; economic growth